“Burnout felt inevitable”: Experiences of university staff in educating the nursing and allied health workforce during the first COVID-19 waves - O'Brien, Lisa; Tighe, Josephine; Doroud, Nastaran; Barradell, Sarah; Dowling, Leah; Pranata, Adrian; Ganderton, Charlotte; Lovell, Robin; Hughes, Roger (Frontiers in Public Health, 2023)
Maintaining progress in the face of looming burnout during the first two years of the COVID-19 pandemic was crucial for the health workforce, including those educating the next generation of health professionals. The experiences of students and healthcare practitioners have been explored to a greater degree than the experiences of university-based health professional educators. This qualitative study examined the experiences of nursing and allied health academics at an Australian university during COVID-19 disruptions in 2020 and 2021 and describes the strategies that academics and/or teams implemented to ensure course continuity. Academic staff from nursing, occupational therapy, physiotherapy, and dietetics courses at Swinburne University of Technology, Australia provided narratives regarding the key challenges and opportunities they faced. The narratives highlighted the strategies generated and tested by participants amidst rapidly changing health orders and five common themes were identified: disruption; stress; stepping up, strategy and unexpected positives, lessons, and legacy impacts. (1) Participants noted challenges related to student engagement in online learning and ensuring the acquisition of discipline-specific practical skills during periods of lock-down. Staff across all disciplines reported increased workload associated with converting teaching to on-line delivery, sourcing alternative fieldwork arrangements, and dealing with high levels of student distress. Many reflected on their own expertise in using digital tools in teaching and their beliefs about the effectiveness of distance teaching for health professional training. Ensuring students were able to complete required fieldwork hours was particularly challenging due to constantly changing public health orders and conditions and staffing shortages at health services. This was in addition to illness and isolation requirements further impacting the availability of teaching associates for specialist skills classes. Solutions such as remote and blended learning solutions, telehealth, and simulated placements were rapidly implemented in some courses especially where fieldwork could not be rescheduled or amended at the health settings. The implications and recommendations for educating and ensuring competence development in the health workforce during times when usual teaching methods are disrupted are discussed.